Perbandingan Metode Certainty Factor Dengan Forward Chaining Pada Sistem Pakar Skrining Kehamilan Resiko Tinggi - Hidra Amnur; Indri Rahmayuni; Yasri Aldi (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2023)
Every pregnancy has a different level of risk. Many pregnant women do not know the risks of their pregnancy so that it can cause death for the baby or for the pregnant woman. Therefore we need an expert system that can help detect early risks of these pregnancies. The use of the Poedji Rochjati Score Card in determining high risk pregnancies with reference to the values contained in the Poedji Rochjati Score. With the design of this expert system, it is hoped that it can help pregnant women in knowing the early risks of the pregnancy they are carrying, whether they have a high risk or not for their pregnancy. The use of the Certainty Factor and Forward Chaining methods in making an expert system is expected to assist in making decisions later for pregnant women who will carry out the delivery process so as to avoid risky pregnancies and can carry out treatment quickly and precisely. The test results from the high-risk pregnancy screening expert system from the data tested using the Certainty Factor method are 100%, while the Forward Chaining accuracy rate is 80%.